Theoretical foundations of the modern paradigm of digitalization of the Ukrainian economy - Shkilniak, Kostyantyn (Herald of Economics, 2024)
Introduction. Nowadays, more and more attention is paid to the problems of digitalization of the economy, the characteristic features of which are the process during which the electronic information environment develops and the latest technologies. Under current conditions, Ukraine is the only one among European states that does not have sufficient digital resources for its complete transfer to the rails of the digital economy. Not the biggest reason why this process slowed down was the full-scale invasion and hostilities, due to which the Ukrainian economy has significant costs (losses), as well as the process that would allow it to transform into the latest digital environment. Because of such trends, there is an urgent need to identify the current problems of the process during which the Ukrainian digital economy is being formed, the main trends and perspectives of how it should develop, moving in the direction of European integration, are maturing.Purpose. The purpose of the article is to reveal the theoretical foundations of the modern paradigm of digitalization of the Ukrainian economy.Methods. In the process of writing this article, the following methods were used: methods of analysis and synthesis (for the purpose of a thorough study of the essence of digitalization of the economy), a graphic method (for the purpose of providing the main definitions of this concept by various Ukrainian scientists), a generalization method, a complex and systematic approach, and an abstract-logical method (for the purpose of formulating conclusions and prospects for further research).Conclusions. The essence of the concept of “digital economy” is revealed and it is determined that it is expedient to consider it as a separate sector of the economy, where business entities conduct economic activity using information and communication and digital technologies, and the leading means (factors) of production are digital (electronic, virtual) data (numerical and text). At the same time, it was established that digitalization should be understood as a process related to the active formation, use, and improvement of technologies specializing in information and communication content.Discussion. Prospects for further research are the study of modern trends in the use of information and communication technologies during digitalization, which has been actively gaining momentum in recent years.